Does the morphology of the ear of the Chinese bamboo rat (Rhizomys sinensis) show "Subterranean" characteristics?. (16th February 2016) - Pleštilová, Lucie; Hrouzková, Ema; Burda, Hynek; Šumbera, Radim
ABSTRACT: In spite of the growing interest in rodents with subterranean activity in general and the spalacids (Spalacidae) in particular, little is known about the biology of most members of this clade, such as the Chinese bamboo rat ( Rhizomys sinensis ). Here, we analyzed the ear morphology of R. sinensis with respect to hearing specialization for subterranean or aboveground modes of communication. It is well‐known that ecology and style of life of a particular species can be reflected in morphology of its ear, its hearing and vocalization, so we expect that such information could provide us insight into its style of life and its sensory environment. The ratio between the eardrum and stapedial footplate areas, which influences the efficiency of middle ear sound transmission, suggests low hearing sensitivity, as is typical for subterranean species. The cochlea had 3.25 coils and resembled species with good low frequency hearing typical for subterranean mammals. The length of the basilar membrane was 18.9 ± 0.8 mm and its width slowly increased towards the cochlear apex from 60 to 85 μm. The mean density of outer hair cells was 344 ± 22 and of inner hair cells 114 ± 7.3 per 1 mm length of the organ of Corti, and increased apically. These values (except for relatively low hair cell density) usually characterize ears specialized for low frequency hearing. There was no evidence for an acoustic fovea. Apart of low hair cell density which is common in aboveground animals, this species has also relatively large auricles, suggesting the importance of sound localization during surface activity. The ear of the Chinese bamboo rat thus contains features typical for both aboveground and subterranean mammals and suggests that this spalacid has fossorial habits combined with regular aboveground activity. J. Morphol. 277:575–584, 2016. © 2016 Wiley Periodicals, Inc.